Evaluation of Proanthocyanidins from Kiwi Leaves (Actinidia chinensis) against Caco-2 Cells Oxidative Stress through Nrf2-ARE Signaling Pathway - Ji-Min Lv; Mostafa Gouda; Xing-Qian Ye; Zhi-Peng Shao; Jian-Chu Chen (MDPI AG, 2022)
Proanthocyanidins (PAs) are considered to be effective natural byproduct and bioactive antioxidants. However, few studies have focused on their mode of action pathways. In this study, reactive oxygen species (ROS), oxidative stress indices, real-time PCR, Western blotting, confocal microscopy, and molecular docking were used to investigate the protective effect of purified kiwi leaves PAs (PKLPs) on Caco-2 cells' oxidative stress mechanisms. The results confirmed that pre-treatment with PKLPs significantly reduced H2O2-induced oxidative damage, accompanied by declining ROS levels and malondialdehyde (MDA) accumulation in the Caco-2 cells. The PKLPs upregulated the expression of antioxidative enzymes (GSH-px, CAT, T-SOD) and the relative mRNA (Nrf, HO-1, SOD-1, CAT) of the nuclear factor erythroid 2-related factor (Nrf2) signaling pathway. The protein-expressing level of the Nrf2 and its relative protein (NQO-1, HO-1, SOD-1) were significantly increased (p < 0.05) in the PKLPs pre-treatment group compared to the model group. In conclusion, the novelty of this study is that it explains how PKLPs' efficacy on the Nrf2-ARE signaling pathway, in protecting vital cells from oxidative stress, could be used for cleaner production.